5.07 - The Potential of Vegetal Biomass for Biomolecules Production - Antunes, F. A.F.; Rocha, T. M.; Philippini, R. R.; Martiniano, S. E.; Prado, C. A.; Mier-Alba, E.; Hernandez-Perez, A. F.; Jofre, F. M.; Abdeshahian, P.; Ribeaux, D. R.; Castro-Alonso, M. J.; Balbino, T. R.; et al. (Elsevier, 2022)
The awareness of global warming, fossil scarcity and pollution are some current eminent burdens which are necessary to be acknowledged in order to find alternative solutions to mitigate its detrimental impacts. Taking this into account, this article focuses on displaying a historical overview, critical trends, recent challenges and employment of vegetal biomass as feedstock for the sustainable and environmentally friendly production of promising microbial-derived molecules through fermentative strategies. Among, bioethanol, xylitol, biopolymers, biosurfactants, organic acids and others such as butanol, butanediol, single cell protein and biopigments will be elucidated. Nevertheless, each one of these biomolecules presents specific applications.
Keywords: Bio-pigments; Bioethanol; Biomass biomolecules; Biopolymers; Biosurfactants; Butanediol; Butanol; Organic acids; Single cell protein; Xylitol